Protective effect of ursodeoxycholic acid on COVID-19 in patients with chronic liver disease - Li, Yanyan; Zhu, Na; Cui, Xinyu; Lin, Yingying; Li, Xin (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: Ursodeoxycholic acid (UDCA) may reduce susceptibility to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection by downregulating host receptors, based on recent experimental investigation results. This study aimed to determine the potential protective effect of UDCA on SARS-CoV-2 infection in patients with chronic liver disease. Methods: Patients with chronic liver disease receiving UDCA (taking UDCA ≥ 1 month) at Beijing Ditan Hospital between January 2022 and December 2022 were consecutively enrolled. These patients were matched in a 1:1 ratio to those with liver disease not receiving UDCA during the same period using a propensity score matching analysis with nearest neighbor matching algorithm. The risk of developing coronavirus disease 2019 (COVID-19) was compared between the two matched cohorts of 225 UDCA users and 225 non-UDCA users. Results: In the adjusted analysis, the control group was superior to the UDCA group in COVID-19 vaccination rates and liver function indicators, including γ-glutamyl transpeptidase and alkaline phosphatase (P < 0.05). UDCA was associated with lower incidence of SARS-CoV-2 infection (UDCA 85.3% vs. control 94.2%, P 0.002), more mild cases (80.0% vs. 72.0%, P 0.047) and shorter median time from infection to recovery (5 days vs. 7 days, P < 0.001). Logistic regression analysis showed that UDCA was a significant protective factor of COVID-19 infection (OR: 0.32, 95%CI: 0.16-0.64, P = 0.001). Besides, diabetes mellitus (OR: 2.48, 95%CI: 1.11-5.54, P = 0.027) and moderated/severe infection (OR: 8.94, 95%CI: 1.07-74.61, P = 0.043) were more likely to prolong the time from infection to recovery. Conclusion: UDCA therapy might be beneficial for reducing COVID-19 infection risk, mitigating symptoms and shortening course in patients with chronic liver disease. However, further large clinical researches were required to validate these findings.